Psoriasis drug use survey - Dayem, Enas Maytham; Haseeb, Dhuha Ali; Ali, Aya Baset; Fleih, Ali Mohammed; Ali, Fatima Kareem; Hameed, Mohammed Fareed (Journal of Pharmacology and Drug Development, 2024)
Psoriasis is a chronic immuno-mediated inflammatory disease of 2.3% prevalence in Iraqi the etiology of the disease is not identified well. A wide variation in disease picture and response to treatment occur due to the complexity of the disease. The study includes 75 male and female people diagnosed with psoriasis. General data and treatment used have been analyzed. A questionnaire is prepared. The study shows that there were twenty-one patients aged between 15 and 24 years, thirty-three patients aged between 25 and 34 years, eight patients aged between 35 and 44 years, and thirteen patients were identified as being older than 44 years. The study shows that the distribution of patients is such that fifty-five percent are male, while forty-five percent are female. Betamethasone was most steroid used. Most of the patients repeat the treatment courses more than two times and most of the patients participated in the study use only one drug. In Conclusion both topical and systemic treatment is used and mostly steroids were the common used group.